Long-term observational study of sporadic inclusion body myositis. - Benveniste, O; Guiguet, M; Freebody, J; Dubourg, O; Squier, W; Maisonobe, T; Stojkovic, T; Leite, M; Allenbach, Y; Herson, S; Brady, S; Eymard, B; et al. (2011)
We describe a long-term observational study of a large cohort of patients with sporadic inclusion body myositis and propose a sporadic inclusion body myositis weakness composite index that is easy to perform during a clinic. Data collection from two groups of patients (Paris and Oxford) was completed either during a clinic visit (52%), or by extraction from previous medical records (48%). One hundred and thirty-six patients [57% males, 61 (interquartile range 55-69) years at onset] were included. At the last visit all patients had muscle weakness (proximal British Medical Research Council scale <3/5 in 48%, distal British Medical Research Council scale <3/5 in 40%, swallowing problems in 46%). During their follow-up, 75% of patients had significant walking difficulties and 37% used a wheelchair (after a median duration from onset of 14 years). The sporadic inclusion body myositis weakness composite index, which correlated with grip strength (correlation coefficient: 0.47; P < 0.001) and Rivermead Mobility Index (correlation coefficient: 0.85; P < 0.001), decreased significantly with disease duration (correlation coefficient: -0.47; P < 0.001). The risk of death was only influenced by older age at onset of first symptoms. Seventy-one (52%) patients received immunosuppressive treatments [prednisone in 91.5%, associated (in 64.8%) with other immunomodulatory drugs (intravenous immunoglobulins, methotrexate or azathioprine) for a median duration of 40.8 months]. At the last assessment, patients who had been treated were more severely affected on disability scales (Walton P = 0.007, Rivermead Mobility Index P = 0.004) and on the sporadic inclusion body myositis weakness composite index (P = 0.04). The first stage of disease progression towards handicap for walking was more rapid among patients receiving immunosuppressive treatments (hazard ratio = 2.0, P = 0.002). This study confirms that sporadic inclusion body myositis is slowly progressive but not lethal and that immunosuppressive treatments do not ameliorate its natural course, thus confirming findings from smaller studies. Furthermore, our findings suggest that immunosuppressant drug therapy could have modestly exacerbated progression of disability. The sporadic inclusion body myositis weakness composite index might be a valuable outcome measure for future clinical trials, but requires further assessment and validation.